The Effect of Organizational Support and Work Environment on Employee Retention with Employee Involvement as an Intervening Variable at RSKM I - Suharti Suharti; Wahyuni Dian Purwati; Rian Adi Pamungkas (Digital Innovation : International Journal of Management, 2025)
Background: HR plays an important role as an organizational manager. HR is an important asset for an organization. In hospitals, retaining competent employees is the key to maintaining service quality. Employee retention is an important challenge in public health services. Objective: to analyze the influence of Organizational Support (OS) and Work Environment (WE) on Employee Retention (ER) with Employee Engagement (EE) as an intervening variable. Method: This study uses a quantitative method with a cross-sectional approach. Data analysis: Index analysis using three box methods, the analysis method using SEM - PLS. Population and Sample: The population in this study were all nurses at RSKM I totaling 112, with a saturated sample, and 100 respondents who met the inclusion criteria. Results: The results showed that there was an influence of OS, WE and EE simultaneously on ER (p = 0.000), there was a significant influence of OS on ER (p = 0.000), there was a significant influence of WE on ER (p = 0.000), there was a significant influence of OS on EE (p = 0.000), there was an influence of WE on EE (p = 0, 000), there was a significant influence of EE on ER (p = 0, 000), there was an influence of OS on ER mediated by EE (p = 0.001) there was a significant influence of WE on ER mediated by EE (p = 0.000). Recommendation: The hospital needs to improve the system in providing employee wages, and must pay attention to the facilities needed to support the work of its employees, so that employees in this hospital are more enthusiastic in their work, have a sense of attachment to the hospital, and it is hoped that employee retention will also increase.